What Are the Maccabean Insurgents Fighting For? The Theological Meaning of νομίμων in 1 Macc 3:21 - Nawrot, Janusz (The Biblical Annals, 2023)
In the discussed verse 1 Macc 3:21, there are two main motivations for the struggle of Judah Maccabee and his compatriots against the Seleucid army of Antiochus IV Epiphanes. The text combines the struggle for the physical existence of Jews with the defence of native customs established on the foundations of the Mosaic Law. There is a clear indissolubility of life and faith in the Jewish consciousness. One cannot survive without one’s own religious tradition, which is the basis of national identity. This article aims to explore the meaning of the Greek adjective νόμιμος, -η, -ον, appearing in the analysed verse of the the book, as substantive (τὸ) νόμιμον, "custom" especially in the plural τὰ νόμιμα, "customs, usages, norms". This term will be presented from a theological and historical perspective in search of an answer to the question about its content and implied meaning in the speech of Judah to his countrymen before the beginning of the battle of Beth-Choron. This content will be both the justification of the struggle undertaken and its importance in the history of Israel in the middle of the 2nd century BC.